Soil Factor Influencing Mangrove Forest Community Occurence in Talidendang Besar, Riau - Cecep Kusmana; Supiandi Sabiham (Department of Forest Resources Conservation and Ecotourism - IPB University, 1991)
This study was undertaken to investigate the soils factors influencing the mangrove forest community occurrence in Talidendang Besar, Riau. One sample plot of 50 m x 50 m was established at hguiera panlifora community. B. se ngulacommunity, and mixed B. scxangula - Nypa fnrticans community to explore its vegetation composition and soil characteristics. The soil factors such as pII, EC (electrical conductivity), 70 K. '% Na, C-organic, N-total, NH4 (ammonia), and CEC (cation exchange capacity) were regarded as soil factors to be important in influencing the occurrence pattern of mangrove forest community in Talidendang Besar. hau. Keywords: mangrove, Talidendang Besar, Riau, forest communig.